Hitaveita Reykjavikur and the Nesjavellir Geothermal Co-Generation Power Plant - Lund, John W. (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 2005)
When Ingólfur Arnarson sighted land on the voyage which would make him the first settler in Iceland, he threw the pillars of his high seat overboard and relied on the gods to direct him to where he should settle. His slaves found them washed ashore in a bay where “smoke” rose out of the ground. Therefore, they called it Reykjavik, “Smoky Bay.” But the smoke after which Iceland’s capital is named was not the result of fire, but was rather steam rising from hot springs. Ancient records only mention the use of geothermal springs for washing and bathing. The best known examples are the Thvottalaugar (washing pools) in what is now Laugardalur in Reykjavik, and the hot pool where saga writer Snorri Sturluson bathed at his farm in Reykholt in western Iceland